The Evolution of Organizational Management Practices in the Digital Era: A Comprehensive Review - Kavita Chaudhary; Aziz Khan (Journal of Advanced Research in HR and Organizational Management, 2025)
The digital revolution has redefined organisational management across industries. Digital technologies such as artificial intelligence (AI), big data, and cloud computing have transformed how organisations design their structures, manage employees, and make decisions. This review examines the evolution of organisational management practices in the digital era, exploring the drivers, enablers, and challenges of digital transformation. The analysis highlights major changes in leadership, human resource management, culture, and performance management. Findings reveal that successful organisations in the digital age adopt agile, data-driven, and human-centred approaches. The review concludes by identifying future research directions focused on sustainable digital transformation and leadership adaptability.